Granice wolności w środkach masowego przekazu - Herynk Skorowski (Jesuit University Ignatianum in Krakow, 2017)
The Author of the article attempts to answer two fundamental questions: where and what are the limits of freedom in the mass media, and are there any limits of freedom in reception and usage of the mass media? The Author searches for the answer to the ﬁ rst question on three planes. The ﬁ rst one is the passing of information, which aims at accuracy and veracity of messages conveyed. On this plane the limit of freedom is, ﬁ rst of all, the good of the very information, as well as the good of man, who is its receiver. It also important that the information passed respects human fundamental rights, including his dignity, and is useful for him. On the other hand, false information, violating fundamental rights and human dignity lies, according to the Author, beyond set limits of freedom of the mass media. Another plane, on which the limits of freedom should be set and preserved, is the plane of passing and disseminating knowled ge, where the aim is passing the truths concerning man, the sense of his life, his place in the world, and speciﬁ c values. The Author indicates that these have to be substantiated and hard truths, truths, which will enrich man within the scope of his views and his outlook on life. Beyond aforementioned limits of freedom there is manipulation of man and his world of beliefs. The third plane determining the limits of freedom serving the mass media is moral sphere consisting in shaping hierarchies of moral values.